(untitled) (Международный научный журнал «Инженер», 2026)
Filters used in industrial enterprises for wastewater treatment have become unusable due to long-term noncompliance with technical regulations and improper use during operation. This mainly involves the failure to wash, replace, and inspect installed filters in a timely manner. This article examines the solution to an effective method for washing filter cartridges. In the first experiment of the study, when the filters were washed with water at a temperature of 15-20 ºС, the washing time was 16-25 minutes (long term). The solution to the above problem was the method of increasing the temperature in qualitative laboratory experiments. The results of this method show that it is very useful for washing oil and oil products and surfactants remaining in filter cartridges in hightemperature water. The reason is that at high temperatures, oil and oil products and surfactants melt and separate from the surfaces of filter cartridges, as a result, the washing coefficient of filter cartridges is higher than the washing coefficient with low-temperature water. It was proven that for the filter loads used in the article, changing the temperature of the wash water in counterflow conditions from the normal water temperature (15-20 ºС) to a higher temperature (50-60 ºС) reduces the filter washing time by a factor of 3.